Contact Deformation of Alumina. (14th November 2012) - Bhattacharya, Manjima; Mukhopadhyay, Anoop Kumar
Abstract : The study of contact-induced deformations during hardness evaluation and the subsequent damage mechanisms of alumina under low loads deserves significant importance for its applications as wear-resistant inserts, biomedical implants, thin films, and armour plates, because the contact-induced brittle failure is an issue of major scientific concern that prevents their widespread commercial applications. However, the studies on hardness of dense, coarse grain alumina at ultralow load, for example, 1 N, are still lacking. Therefore, the present study was conducted on a dense ( 95% of theoretical) coarse-grain ( 20 μ m) alumina at a low peak load of 1 N with varying loading rates (10 −3 –10 0 N·s −1 ) applied in depth sensitive indentation experiments. The results showed profuse presence of multiple micro-pop-in and pop-out events possibly linked to dislocation nucleations underneath the indenter. The critical resolved shear stress (τ CRSS ) was found to enhance with the increase in applied loading rates. The occurrences of the localized shear deformation band formation and microcracking in and around the indentation cavity were explained in terms of the correlation between the nanoscale plasticity events, the small magnitude of (τ CRSS ), the maximum shear stress (τ max ) developed just underneath the indenter, and the dislocation loop radius (R d ).